The martyred sultan: Tuman Bay II in André Thevet's Les vrais pourtraits et vies des hommes illustrés. Issue 1 (2nd January 2017) - Milwright, Marcus
Abstract: The last ruler of the Mamluk dynasty, Tuman Bay II, was executed in 1517 by order of the Ottoman sultan Selim I. Although Tuman Bay's rule lasted only a year, his biography attracted the interest of numerous European scholars. He appeared in sixteenth-century biographical encyclopaedias, most notably those of Paolo Giovio and André Thevet. Where Giovio's portrait of Tuman Bay showed the sultan dressed in an outfit appropriate to his status, including an elaborate turban, the image in Thevet's Les vrais pourtraits (1584) is more unusual. Thevet's illustration shows the sultan bound in ropes, bare-headed and looking upward in a beseeching manner that invites comparison with European representations of Christian martyrs. This article examines visual sources and primary texts (European and Arabic) for the representation of Tuman Bay in Les vrais pourtraits and in other works published by Thevet. It concentrates on the period of the sultan's captivity and execution, suggesting ways in which Thevet might have encountered popular reconstructions of these events in Egypt or Turkey.